Синтез 2-арил-4-арилиден-5(4H)-оксазолонов, катализируемый солями кобальта - А. Р. Манвелян (ՀՀ ԳԱԱ հրատ.)
Установлено каталитическое влияние ацетата и хлорида кобальта в синтезе ненасыщенных и насыщенных 5(4Н)-оксазолонов из N-замещенных аминокислот в присутствии уксусного ангидрида. Ուսումնասիրված է կոբալտի որոշ աղերի (ացետատ, քլորիդ) կատալիտիկ ազդեցությունը N-տեղակալված ամինոթթուների և քացախանհիդրիդի փոխազդեցությամբ հագեցած և չհագեցած 5(4H)-օքսազոլոնների առաջացման ռեակցիայի վրա: The effect of cobalt acetate and chloride on formation of both saturated and unsaturated 5(H)-oxazolones in interaction of N-substituted amino acids with acetic anhydride has been studied. The investigations were carried out both at room temperature in ethanol medium and in the absence of a solvent under conditions of microwave radiation. It has been established that in both cases cobalt acetate affords relatively high yields of target products.
Keywords: Biochemistry; Organic Chemistry